Synthesis and antiviral evaluation of 2′,2′,3′,3′-tetrafluoro nucleoside analogs - Sari, Ozkan (Tetrahedron Lett, 2017)
Herein, we report the synthesis of novel 2′,2′,3′,3′-tetrafluorinated nucleoside analogs along with their phosphoramidate prodrugs. A tetrafluoro ribose moiety was coupled with different Boc/benzoyl-protected nucleobases under Mitsunobu conditions. After deprotection, tetrafluorinated nucleosides 13b, 14b, 20b–22b were reacted with phenyl-(isopropoxy-L-alaninyl)-phosphorochloridate to afford corresponding monophosphate prodrugs 24b–28b. All synthesized compounds were evaluated against several DNA and RNA viruses including HIV, HBV, HCV, Ebola and Zika viruses.